A adamantylamine bisphenol monomer modified polyaryletherketone and a preparation method and application thereof

CN122897983APending Publication Date: 2026-10-13JILIN JUKE HIGH TECH MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611381917.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

传统双羟基芳基金刚烷单体(例如CAS编号为37677-93-3的1,3-双(4-羟基苯基)金刚烷以及CAS编号为52211-74-2的2,2-双(4-羟基苯基)金刚烷)虽然能够实现上述改性,但其价格较高、合成路线较长、供应渠道有限,难以实现工业化应用

Benefits of technology

[0025]本发明所述金刚烷胺双酚单体改性聚芳醚酮,将含较低成本的金刚烷胺基双酚单体共价引入PEEK类聚芳醚酮分子链中。所得共聚物分子链中同时含有由二酚单体与二卤代芳香族酮单体缩聚形成的芳香醚酮主链结构、金刚烷笼状结构和含氮界面作用位点,从而在低介电性能、热稳定性、金属结合力和加工性能之间取得综合平衡。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897983A_ABST
    Figure CN122897983A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of high-performance engineering plastics and electrical insulation materials, and particularly relates to adamantylamine bisphenol monomer modified polyaryletherketone and a preparation method and application thereof. The adamantylamine bisphenol monomer modified polyaryletherketone is a kind of polyaryletherketone, which is covalently introduced into the molecular chain of PEEK type polyaryletherketone by a bisphenol monomer containing adamantylamine group structure. The obtained polymer molecular chain contains polyaryletherketone main chain structure, adamantane cage structure and nitrogen-containing interface interaction site, thereby achieving a comprehensive balance between low dielectric performance, thermal stability, dimensional stability, metal bonding force and processing performance. In the polymer containing secondary amine structure, N-H can provide hydrogen bond and metal interface interaction site; when the nitrogen atom is further alkylated, the tertiary amine structure can further reduce the risk of active hydrogen side reaction, and adjust the material polarity and interface interaction ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of high-performance engineering plastics and electrical insulation materials, specifically relating to an adamantaneamine bisphenol monomer-modified polyarylether ketone and its preparation method and application. Background Technology

[0002] Polyetheretherketone (PEEK) and related polyaryletheretherketone (PAGEK) materials possess excellent heat resistance, mechanical properties, electrical insulation properties, and chemical corrosion resistance, and are widely used in wire and cable, electronics, aerospace, precision machinery, and high-performance engineering plastics. With the development of new energy vehicle flat copper wire motors, high-frequency electronic devices, and heat-resistant insulating structural components, higher requirements are being placed on PAGEK materials in terms of low dielectric constant, low loss, wear resistance, and metal-metal interface bonding.

[0003] Conventional PEEK has a high melting point, and its melt processing temperature is usually high, which can easily lead to problems such as increased energy consumption, narrow processing window, copper conductor oxidation, increased internal stress in the coating, and pinhole defects. By introducing low-polarity, large-volume, or rigid structural units into the PEEK polyaryletherketone backbone, the chain segment regularity, crystallization behavior, melting behavior, and dielectric response can be controlled.

[0004] Adamantane has a rigid cage-like structure with low polarity, low polarizability, and a large steric volume effect. Introducing it into the backbone of polyaryletherketones is beneficial for reducing dielectric constant and dielectric loss, as well as improving heat resistance and wear resistance. Although traditional dihydroxyaryletherane monomers (such as 1,3-bis(4-hydroxyphenyl)adamantane with CAS number 37677-93-3 and 2,2-bis(4-hydroxyphenyl)adamantane with CAS number 52211-74-2) can achieve the above modifications, they are expensive, have long synthetic routes, and limited supply channels, making industrial application difficult.

[0005] Furthermore, the interfacial adhesion between conventional PEEK and copper conductors is limited. In applications such as magnet wire, flat copper wire, and metal surface insulation, conductor surface treatment, adhesive layers, or multilayer insulation structures are typically relied upon to improve adhesion. These methods not only increase process complexity but also fail to simultaneously address the comprehensive balance between low dielectric properties, melt processing methods, metal bonding strength, and insulation reliability at the polyaryletherketone molecular structure level.

[0006] Therefore, there is a need in the art to develop a novel low-cost polyaryletherketone copolymer with adamantane-amine-containing bisphenol monomers as the modifying unit, which can improve dielectric properties and enhance metal bonding while maintaining the heat-resistant skeleton and electrical insulation properties of PEEK-type polyaryletherketone copolymers, and also meet the needs of melt processing and solution processing applications. Summary of the Invention

[0007] The first objective of this invention is to provide a polyaryletherketone modified with adamantane bisphenol monomer, wherein the modified polyaryletherketone is modified with a low-cost adamantane bisphenol monomer, and the modified polyaryletherketone achieves a comprehensive balance between low dielectric properties, thermal stability, metal bonding strength and processability. The second objective of this invention is to provide a method for preparing the above-mentioned adamantane bisphenol monomer modified polyarylether ketone, wherein the method uses adamantane bisphenol monomer, dihydroxy aromatic monomer and dihaloaromatic ketone monomer as raw materials, and prepares the product through a nucleophilic substitution condensation reaction, which has the advantages of being simple and easy to operate. A third objective of this invention is to provide the application of the above-mentioned adamantane bisphenol monomer-modified polyarylether ketone in the preparation of electrical insulating materials, low dielectric materials, wear-resistant materials, metal surface coating materials, or high-performance engineering plastic materials.

[0008] To solve the above-mentioned technical problems, the present invention provides an adamantane bisphenol monomer modified polyarylether ketone, wherein the polymerization raw materials of the modified polyarylether ketone include a bisphenol monomer, a dihaloaromatic ketone monomer, and a salt-forming agent. The bisphenol monomer includes adamantane bisphenol monomer having the structure shown in formulas (I)-(II): ,

[0009] (I) (II) in: R1, R2, R3, and R4 are independently H, -OH, or C1-C4 alkyl groups, and there is one and only one -OH group between R1 and R2, and one and only one -OH group between R3 and R4. R5 and R6 are independently H or C1-C4 alkyl groups; R7 is H or a C1-C4 alkyl or adamantane methyl group.

[0010] Specifically, in the adamantane bisphenol monomer-modified polyarylether ketone, the adamantane bisphenol monomer includes one of the following structures: , , , , , .

[0011] The adamantane bisphenol monomer contains two phenolic hydroxyl groups, an adamantane cage structure, and a secondary or tertiary amine structure. The two phenolic hydroxyl groups can participate in the nucleophilic substitution condensation reaction of polyaryletherketones; the adamantane cage structure provides rigidity, low polarity, large volume, and free volume effects; when R7 is H, the polymer chain retains the secondary amine NH structure, which can provide hydrogen bonds, dipoles, coordination sites, or Lewis acid-base interaction sites, which is beneficial for improving the glass transition temperature and metal interface bonding; when R7 is C1-C4 alkyl or adamantane methyl, the resulting monomer has a tertiary amine structure, which can reduce the risk of side reactions of active hydrogen during high-temperature condensation and regulate the polarity, hygroscopicity, and interfacial interaction ability of the polymer. Preferably, N-(adamantane-1-yl)-bis(4-hydroxyphenyl)methylamine and N-(adamantane-1-yl)-N-methyl-bis(4-hydroxyphenyl)methylamine are used, denoted as Ad-NH-CH(PhOH)2 and Ad-N(CH3)-CH(PhOH)2, respectively.

[0012] Specifically, in the polymerization raw materials for the adamantaneamine bisphenol monomer-modified polyarylether ketone, the bisphenol monomer, based on its total molar amount, comprises: The adamantane bisphenol monomer is 3-100 mol%; Dihydroxy aromatic monomers 0-97 mol% The dihydroxy aromatic monomer includes at least one of hydroquinone, resorcinol, or biphenyl.

[0013] When the adamantane bisphenol monomer is used in polyaryletherketones suitable for melt processing and injection molding, its content is preferably 3-20 mol%, more preferably 10-20 mol%; while when it is used in polyaryletherketones suitable for solution processing, coating and casting, the content of the adamantane bisphenol monomer is preferably 50-100 mol%.

[0014] In the polyaryletherketone modified with adamantane bisphenol monomer, when the adamantane bisphenol monomer content is low (e.g., <5 mol%), the material still maintains good semi-crystallizability and mechanical properties, but the improvement in dielectric properties and copper adhesion is relatively limited. When the adamantane bisphenol monomer content is 10-20 mol%, the synergistic effect of the adamantane structure and the amino structure is more obvious, and the material can achieve a balance between low dielectric loss, high thermal stability, high copper adhesion, and melt processability. When the adamantane bisphenol monomer content is above 50 mol%, the polymer chain segment regularity is significantly reduced, the solubility is enhanced, and it is more suitable for solution coating and casting.

[0015] Specifically, in the raw materials for preparing the adamantaneamine bisphenol monomer-modified polyarylether ketone: The molar ratio of the dihaloaromatic ketone monomer to the diphenol monomer is 0.995-1.005:1; And / or, the molar ratio of the salt-forming agent to the diphenol monomer is 1.02-1.3:1.

[0016] Specifically, in the raw materials for preparing the adamantaneamine bisphenol monomer-modified polyarylether ketone: The dihaloaromatic ketone monomers include at least one of 4,4'-difluorobenzophenone, 4,4'-dichlorobenzophenone, 2,4-difluorobenzophenone, 4-fluoro-4'-chlorobenzophenone, 2-fluoro-4-chlorobenzophenone, 2-chloro-4-fluorobenzophenone, 1,4-bis(4-fluorobenzoyl)benzene or 1,3-bis(4-fluorobenzoyl)benzene; And / or, the salt-forming agent includes at least one of alkali metal carbonates, alkali metal hydroxides, or alkali metal alkoxides. Specifically, it includes, but is not limited to, one or more of potassium carbonate, sodium carbonate, cesium carbonate, sodium hydroxide, potassium hydroxide, and potassium tert-butoxide, preferably potassium carbonate and / or sodium carbonate.

[0017] This invention also discloses a method for preparing adamantane bisphenol monomer-modified polyarylether ketone, wherein the copolymer is prepared by nucleophilic substitution polycondensation reaction of adamantane bisphenol monomer containing an adamantane group, a dihydroxy aromatic monomer, and a dihaloaromatic ketone monomer, comprising the following steps: (1) Under a protective atmosphere, a selected amount of the diphenol monomer, the dihaloaromatic ketone monomer, the salt-forming agent and the reaction solvent are mixed to obtain a mixture; (2) The mixture is heated to the first reaction temperature, so that the diphenol monomer and the salt-forming agent undergo the first reaction to form phenol salt, and the water in the system is removed; (3) Continue heating to the second reaction temperature to allow the phenolate and dihaloaromatic ketone monomers to undergo a second reaction, thereby obtaining a prepolymer; (4) Continue heating to the third reaction temperature to allow the prepolymer to undergo the third reaction, thereby obtaining the condensate; (5) Continue heating to the fourth reaction temperature to allow the condensate to undergo the fourth reaction, thereby obtaining the desired modified polyarylether ketone.

[0018] Specifically, in the preparation method of the adamantane bisphenol monomer-modified polyarylether ketone: The first reaction temperature is 140-180℃, and the first reaction time is 1-3 hours; And / or, the second reaction temperature is 200-240℃, and the second reaction time is 1-3h; And / or, the third reaction temperature is 260-290℃, and the third reaction time is 0.5-12h; And / or, the fourth reaction temperature is 290-320℃, and the fourth reaction time is 0.5-12h.

[0019] The reaction solvent includes at least one of polar aprotic solvents. The aprotic polar solvent is preferably a high-boiling-point aprotic polar solvent suitable for high-temperature polycondensation, including but not limited to one or more of diphenyl sulfone, sulfolane, N-methylpyrrolidone, dimethylacetamide, and dimethyl sulfoxide, preferably diphenyl sulfone and / or sulfolane. The amount of the reaction solvent is sufficient to cover the required amount of the reactants, and is added in adequate quantity.

[0020] The protective atmosphere includes a nitrogen atmosphere or an inert atmosphere, or a combination of both.

[0021] Specifically, the method for preparing the adamantane bisphenol monomer-modified polyarylether ketone further includes the step of preparing the adamantane bisphenol monomer, specifically including the following steps: (a) Under a protective atmosphere, dihydroxybenzophenone, adamantane, a first solvent and an acidic catalyst are mixed and subjected to a condensation reaction under heating conditions to obtain an imine intermediate; (b) Under a protective atmosphere, the imine intermediate, the first reducing agent, and the second solvent are mixed and a first reduction reaction is carried out to obtain an adamantane bisphenol monomer with R7 as shown in formula (I) or (II). (c) Optionally, an aldehyde compound corresponding to the selected R7 structure and a second reducing agent are added, and a second reduction reaction is carried out to obtain an adamantane bisphenol derivative in which R7 is a C1-C4 alkyl or adamantane methyl group as shown in formula (I) or (II).

[0022] Specifically, in the preparation method of the adamantane bisphenol monomer: The dihydroxybenzophenone raw material includes substituted or unsubstituted 4,4'-dihydroxybenzophenone, 2,4'-dihydroxybenzophenone or 2,2'-dihydroxybenzophenone; And / or, the adamantaneamine raw material includes substituted or unsubstituted 1-adamantaneamine, 2-adamantaneamine or its salts; And / or, the molar ratio of the dihydroxybenzophenone raw material to the adamantane raw material is 1:1.0-1.2; And / or, the acidic catalyst is a Lewis acid catalyst, including at least one of p-toluenesulfonic acid, trifluoromethanesulfonic acid, trifluoroacetic acid, boron trifluoride, or aluminum trichloride; And / or, the amount of the acidic catalyst added accounts for 1-1.5 mol% of the molar amount of the dihydroxybenzophenone raw material. And / or, the temperature of the heating condensation reaction is 130-160℃, and the reaction time is 6-12h; And / or, the first solvent includes at least one of toluene, xylene, or chlorobenzene; And / or, the method further includes the steps of neutralizing, washing and / or drying the imine intermediate; And / or, the first reducing agent or the second reducing agent independently includes at least one of sodium borohydride, sodium cyanoborohydride, sodium triacetoxyborohydride, and reducing formate; And / or, the molar ratio of the first reducing agent to the imine intermediate is 1-2:1; And / or, the molar ratio of the second reducing agent to the adamantane bisphenol derivative is 1-2:1; And / or, the aldehyde compounds include at least one of formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, or 1-adamantaneformaldehyde; And / or, the temperature of the first reduction reaction is 25-50°C, and the reaction time is 4-8 hours; And / or, the temperature of the second reduction reaction is 10-30℃, and the reaction time is 2-12h; And / or, the second solvent includes at least one of an alcohol solvent or an ether solvent; And / or, The method further includes the steps of extraction, washing, concentration, recrystallization, column chromatography purification and / or vacuum drying of the derivatives shown in formula (I) or (II); And / or, the protective atmosphere includes a nitrogen atmosphere or an inert atmosphere, or a combination of both.

[0023] The present invention also discloses the application of the adamantane bisphenol monomer-modified polyaryletherketone or the adamantane bisphenol monomer-modified polyaryletherketone prepared by the method in the preparation of electrical insulating materials, low dielectric materials, wear-resistant materials, metal surface coating materials or high-performance engineering plastic materials.

[0024] Specifically, the application materials of the adamantane bisphenol monomer modified polyaryletherketone include one or more of the following: wire and cable insulation layers, flat copper wire outer sheaths, electromagnetic wire insulation layers, low dielectric insulating films, electronic and electrical insulating structural components, injection molded insulating components, hot-pressed insulating films, metal surface insulating coatings, wear-resistant coatings, connector supports, sensor insulating brackets, or high-performance engineering plastic products.

[0025] The adamantaneamine bisphenol monomer-modified polyaryletherketone (PEEK) of this invention covalently introduces a low-cost adamantaneamine bisphenol monomer into the PEEK-type PEEK molecular chain. The resulting copolymer molecular chain simultaneously contains an aromatic ether ketone backbone structure formed by the condensation polymerization of a bisphenol monomer and a dihaloaromatic ketone monomer, an adamantane cage structure, and nitrogen-containing interfacial interaction sites, thereby achieving a comprehensive balance between low dielectric properties, thermal stability, metal bonding strength, and processability.

[0026] The adamantaneamine bisphenol monomer-modified polyaryletherketone (PAEK) of this invention effectively improves dielectric properties. Due to the low polarity, low polarizability, and large free volume effect of the adamantane structure, it reduces dipole polarization and orientation polarization responses in the polymer, thereby lowering the dielectric constant and dielectric loss of the material under high-frequency electric fields. By controlling the proportion of adamantaneamine bisphenol monomer added, excessive introduction of the amine structure can be avoided, which would lead to increased dielectric loss. This effect helps reduce dielectric heating in electronic devices and cable insulation layers, improving service reliability under high-frequency, high-voltage, and high-temperature environments. Furthermore, the low dielectric properties achieved by this invention do not depend on fluorinated side groups or perfluorinated segments, which helps reduce environmental compliance pressures and material recycling pressures associated with fluorinated organic structures, making it more suitable as an environmentally friendly, low-dielectric, high-performance engineering plastic.

[0027] The adamantane amine bisphenol monomer-modified polyaryletherketone (PAEK) of this invention maintains the heat resistance of PAEK. Because the adamantane structure itself has rigidity and high thermal stability, its low-proportion introduction does not significantly weaken the heat-resistant backbone of the PAEK backbone, allowing the resulting material to maintain a high thermal decomposition temperature, high tensile strength, and high tensile modulus. This avoids the problem of a significant decrease in mechanical properties due to simply lowering the melting point, making it suitable for heat-resistant insulation applications.

[0028] Although the crystallinity of the polyarylether ketone modified with adamantane amine bisphenol monomer of the present invention decreases due to the introduction of the third comonomer, the rigidity of the local chain segments can be increased by introducing the rigid adamantane group, thereby increasing the glass transition temperature. Furthermore, the movement of the molecular chain can be suppressed by the hydrogen bonds or dipole interactions formed by the amino group and the ketone carbonyl group or the terminal hydroxyl group, thereby maintaining a certain dimensional stability.

[0029] The adamantaneamine bisphenol monomer-modified polyaryletherketone polymer of this invention exhibits stronger metal-interface interaction capabilities. Because the amine structure in the polymer can form hydrogen bonds, coordination, dipole, or Lewis acid-base interactions with the oxide layer on the copper conductor surface, metal oxides, or polar interfaces, it enhances the bonding force between the polyaryletherketone outer layer and the copper conductor. Compared to traditional 1,3-bis(4-hydroxyphenyl)adamantane and 2,2-bis(4-hydroxyphenyl)adamantane modified systems, the material of this invention exhibits higher interfacial strength with the metal.

[0030] The material obtained by this invention is adaptable to melt or solution processing methods with a wider processing window. The bisphenol monomer containing the adamantaneamine group in this invention has a large volume, rigid cage-like, and non-planar structural characteristic, which can moderately disrupt the regular stacking of polyaryletherketone (PAE) molecular chains, reducing crystal perfection and melting temperature. Therefore, PAE copolymers with low to medium modification ratios can lower the melting point of PAE materials, thereby widening the melt processing window and reducing the processing temperature during melt extrusion, making them suitable for extrusion, injection molding, hot pressing, and cable coating processes. PAE copolymers with high modification ratios exhibit better solution processing capabilities due to decreased chain segment regularity and increased polar interaction sites, making them suitable for coating, impregnation, and casting film formation processes.

[0031] In the modification of polyarylether ketones with adamantane bisphenol monomers described in this invention, compared with traditional dihydroxyarylether bisphenol monomers (such as 1,3-bis(4-hydroxyphenyl)adamantane and 2,2-bis(4-hydroxyphenyl)adamantane), the adamantane bisphenol monomers participating in the modification reaction use dihydroxybenzophenone and adamantane as the main starting materials. A primary reductive amination reaction is performed to form an imine intermediate through condensation and further reduction, preparing a secondary amine-type adamantane bisphenol monomer with R7 as H. Alternatively, a second reduction reaction is carried out with aldehyde compounds to prepare a tertiary amine-type adamantane bisphenol monomer with R7 as C1-C4 alkyl or adamantanemethyl. This avoids direct reliance on traditional dihydroxyarylether bisphenol monomers, which are expensive and have limited supply, and offers advantages such as readily available raw materials, flexible routes, and lower costs. Furthermore, this invention can also obtain a series of bisphenol derivatives containing adamantane groups by selecting different dihydroxybenzophenone isomers, different adamantane amine raw materials, and different N-substituted groups, thereby adjusting the spatial configuration, polarity, hydrogen bonding ability, interfacial interaction ability, and reaction compatibility of the monomers, and has strong structural scalability and application scalability. Attached Figure Description

[0032] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein: Figure 1 The proton nuclear magnetic resonance spectra of the bisphenol monomers containing adamantane amino groups obtained in Examples 1-6 were prepared. 1 H-NMR spectrum; Figure 2 Carbon NMR spectra of the bisphenol monomers containing adamantane amino groups obtained in Examples 1-6 ( 13 C-NMR spectrum; Figure 3 The attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra of the polymers obtained in Examples 4, 8, 9, 10, Comparative Example 1, and Comparative Example 2 are shown. Detailed Implementation

[0033] The present invention is further illustrated by the following embodiments, which are not intended to limit the invention in any way. Any modifications or alterations made to the present invention that are easily implemented by those skilled in the art without departing from the technical solutions of the present invention shall fall within the scope of the claims of the present invention.

[0034] In the following embodiments of the present invention, an adamantane bisphenol monomer synthesized from low-cost, readily available raw materials is provided; the adamantane bisphenol monomer has a structure as shown in formulas (I)-(II): , .

[0035] (I) (II) In the following embodiments of the present invention, a method for preparing the above-mentioned adamantane bisphenol monomer is also provided, using dihydroxybenzophenone and adamantane as substrates, and preparing the desired adamantane bisphenol derivative through one or two reductive amination reactions.

[0036] In the following embodiments of the present invention, a modified polyaryletherketone polymer prepared based on the above-mentioned adamantane bisphenol monomer is also provided. The polymerization raw materials of the modified polyaryletherketone include bisphenol monomer, dihaloaromatic ketone monomer and salt-forming agent. The bisphenol monomers, in terms of their total molar amount, include: 3-100 mol of the adamantane bisphenol monomer; and 0-97 mol of the dihydroxy aromatic monomer.

[0037] In the following embodiments of the present invention, a method for preparing polyarylether ketone modified with adamantane bisphenol monomer as described above is also provided, wherein the copolymer is prepared by nucleophilic substitution polycondensation reaction of adamantane bisphenol monomer containing an adamantane group, a dihydroxy aromatic monomer and a dihaloaromatic ketone monomer.

[0038] Preparation Example 1 This preparation example is used to prepare the bisphenol monomer N-(adamantane-1-yl)-bis(4-hydroxyphenyl)methylamine containing an adamantaneamine group, denoted as Ad-NH-CH(PhOH)2. Its structure and specific synthetic route are as follows: ; .

[0039] To a 5L four-necked flask equipped with a mechanical stirrer, condenser, thermometer, nitrogen delivery tube, and water separator, add 214.2 g (1.000 mol) of 4,4'-dihydroxybenzophenone, 166.4 g (1.100 mol) of 1-adamantaneamine, 1.72 g (0.010 mol) of p-toluenesulfonic acid, and 2L of anhydrous xylene. Purge the system with nitrogen for 30 min to remove air, then heat to reflux under nitrogen protection and react for 10 h. Remove the water generated during the condensation reaction using the water separator to ensure complete condensation of 4,4'-dihydroxybenzophenone and 1-adamantaneamine to form an intermediate containing an adamantaneimine structure.

[0040] After the condensation reaction was completed, the reaction solution was cooled to below 30°C, and some xylene was removed under reduced pressure. Then, an appropriate amount of sodium bicarbonate aqueous solution was added to the system for neutralization, adjusting the pH of the aqueous phase to 7-8 to remove residual acidic catalyst and prevent its adverse effects on subsequent reduction reactions. After neutralization, the two phases in the system were separated, the organic phase was collected, washed with deionized water, dried over anhydrous sodium sulfate, filtered, and the solvent was removed by vacuum distillation to obtain the intermediate Ad-N=C(PhOH)2.

[0041] The obtained intermediate was dissolved in a mixed solvent of 1.5 L anhydrous tetrahydrofuran and 0.8 L anhydrous methanol, and stirred under nitrogen protection. Then, sodium borohydride, totaling 56.7 g (1.500 mol), was added in three batches, with the addition temperature controlled to not exceed 30 °C. After the addition was complete, the reaction was continued at 40 °C for 6 h to allow the imine structure to be fully reduced to the amine structure. After the reaction was complete, excess sodium borohydride was quenched by slowly adding a saturated ammonium chloride aqueous solution, and the pH of the system was adjusted to 8.0 with a sodium bicarbonate aqueous solution.

[0042] The reaction system was extracted multiple times with ethyl acetate. After combining the organic phases, the mixture was washed successively with deionized water and saturated sodium chloride aqueous solution, dried over anhydrous sodium sulfate, and concentrated under reduced pressure to obtain the crude product. The crude product was recrystallized using an ethanol / water or acetone / water system. After filtration, the solid was dried under vacuum at 80°C for 12 h to obtain a white to light yellow solid, namely the bisphenol monomer Ad-NH-CH(PhOH)2 containing an adamantaneamine group.

[0043] In this preparation example, the yield of the obtained monomer can reach 65-90%, and the HPLC purity is not less than 95%, or even not less than 99%. The obtained monomer was confirmed by proton NMR and carbon NMR spectroscopy.

[0044] The monomer obtained in this preparation example can be represented as N-(adamantane-1-yl)-bis(4-hydroxyphenyl)methylamine, denoted as Ad-NH-CH(PhOH)2. This monomer molecule simultaneously contains two phenolic hydroxyl groups, an adamantane cage structure, and an amino group. The two phenolic hydroxyl groups can serve as reaction sites for the nucleophilic substitution condensation polymerization of polyaryletherketones; the adamantane structure provides rigidity, low polarity, and a large free volume effect; and the amino group structure can enhance the interaction between the polymer and metal conductors, fillers, or polar interfaces.

[0045] The bisphenol monomer containing the adamantane amino group obtained in this preparation example can be analyzed by methods such as 1H NMR spectroscopy, 1C NMR spectroscopy, high performance liquid chromatography, differential scanning calorimetry, and thermogravimetric analysis. In the 1H NMR spectroscopy, characteristic peaks of the adamantane skeleton, aromatic hydrogen peaks, and benzylic methylene hydrogen peaks can be observed; thermogravimetric analysis can be used to evaluate the thermal stability of this monomer under subsequent high-temperature polycondensation conditions.

[0046] Preparation Example 2 This preparation example prepares an N-methylated tertiary amine-type bisphenol monomer containing an adamantaneamine group, N-(adamantane-1-yl)-N-methyl-bis(4-hydroxyphenyl)methylamine, denoted as Ad-N(CH3)-CH(PhOH)2, with the following structure: .

[0047] 34.95 g of the secondary amine bisphenol monomer Ad-NH-CH(PhOH)2 (0.100 mol) obtained in Preparation Example 1 was added to a 1 L four-necked flask, along with 400 mL of anhydrous tetrahydrofuran and 200 mL of anhydrous methanol. The mixture was stirred and dissolved under nitrogen protection. The reaction system temperature was controlled at 20 °C, and 10.0 mL of a 37% (w / w) formaldehyde aqueous solution was added dropwise, with the amount of formaldehyde being approximately 0.120 mol, equivalent to 1.2 times the equivalent of the secondary amine group. After the addition was complete, the mixture was stirred at 20 °C for 2 h to allow the secondary amine to fully react with the formaldehyde and form an imine-onium intermediate in situ.

[0048] The reaction system was then cooled to 10°C, and 5.67 g (0.150 mol) of sodium borohydride was added in three batches with stirring, each batch added at 15 min intervals, and the system temperature was kept below 30°C. After the sodium borohydride was added, the reaction system was brought to room temperature and the reaction was continued at 25°C for 6 h. The completion of the reaction was confirmed by thin-layer chromatography; the reaction was considered complete when the starting material spot had essentially disappeared.

[0049] After the reaction was complete, the system was cooled to 4°C, and excess sodium borohydride was quenched by slowly adding a saturated ammonium chloride aqueous solution, controlling the dropping rate to avoid violent gas release. After quenching, the pH of the system was adjusted to 8.0 with sodium bicarbonate aqueous solution, and some methanol and tetrahydrofuran were removed under reduced pressure. Then, ethyl acetate was added for extraction. The organic phase was washed successively with deionized water and saturated brine, dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. The crude product was recrystallized from ethanol / water, methanol / water, or acetone / water, or purified by silica gel column chromatography, and then dried under vacuum at 80°C for 12 h to obtain the N-methylated tertiary amine bisphenol monomer Ad-N(CH3)-CH(PhOH)2, a white solid. In this example, the product yield reached 70-85%, and the HPLC purity was preferably not less than 95% or even not less than 98%.

[0050] Preparation Example 3 The structure of the adamantane bisphenol derivative described in this preparation example is shown below: .

[0051] The preparation method of the adamantane bisphenol derivative described in this preparation example is the same as that in Preparation Example 1, except that the adamantane raw material is selected as 2-adamantaneamine.

[0052] Preparation Example 4 The structure of the adamantane bisphenol derivative described in this preparation example is shown below: .

[0053] The preparation method of the adamantane bisphenol derivative described in this preparation example is the same as that in Preparation Example 1, except that the dihydroxybenzophenone raw material is selected as 2,4'-dihydroxybenzophenone.

[0054] Preparation Example 5 The structure of the adamantane bisphenol derivative described in this preparation example is shown below: .

[0055] The preparation method of the adamantane bisphenol derivative described in this preparation example is the same as that in Preparation Example 1, except that the dihydroxybenzophenone raw material is selected as 2,2'-dihydroxybenzophenone.

[0056] Preparation Example 6 The structure of the adamantane bisphenol derivative described in this preparation example is shown below: .

[0057] The preparation method of the adamantane bisphenol derivative described in this preparation example is the same as that in Preparation Example 2, except that the aldehyde reagent is changed from formaldehyde to 1-adamantaneformaldehyde.

[0058] Experimental Example 1 This experimental example confirms the structure of the bisphenol monomers containing the adamantane amino group obtained in Preparation Examples 1-6. In this example, 1H NMR and 1C NMR spectra were used to characterize the structures of the products obtained in Preparation Examples 1-6. 1H NMR was used to confirm the aromatic hydrogen, adamantane skeleton hydrogen, benzylic methylene hydrogen, or N-methyl hydrogen. The test solvent was DMSO-d6, and TMS was used as an internal standard for chemical shifts.

[0059] The proton and carbon NMR spectra of the bisphenol monomers containing the adamantaneamine group obtained in Preparation Examples 1-6 are attached. Figure 1 and attached Figure 2 As shown.

[0060] It can be seen that, Figure 1 The signal at 2.50 ppm belongs to the residual proton peak of DMSO-d6, the signal at 3.33 ppm belongs to the water peak, and the signal at 0 ppm belongs to TMS. Figure 2 The signal at 39.5 ppm belongs to the carbon peak of DMSO-d6 solvent, and the signal at 0 ppm belongs to TMS.

[0061] In the 1H NMR spectrum of the secondary amine bisphenol monomer Ad-NH-CH(PhOH)2 obtained in Preparation Example 1, a broad peak of active hydrogen at the phenolic hydroxyl group, a hydrogen signal of the para-substituted aromatic ring, an Ar2CH-NH benzylic CH signal at approximately 5.0 ppm, a broad NH peak at 4.2-4.7 ppm, and a hydrogen signal of the adamantane skeleton were observed. No characteristic C=N carbon signal was observed in its 1C NMR spectrum, and an Ar2CH-NH carbon signal appeared at 63-68 ppm, indicating that the imine structure had been reduced to the secondary amine structure.

[0062] In the 1H NMR spectrum of the N-methylated tertiary amine bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2, the broad NH peak disappeared, and a characteristic N-CH3 singlet appeared at about 2.2 ppm; in its 1C NMR spectrum, an N-CH3 carbon signal appeared at 37-42 ppm, and an Ar2CH-N carbon signal appeared at 68-72 ppm, indicating that the secondary amine structure underwent further N-methylation reaction.

[0063] Preparation Example 3 is an isomerized adamantane bisphenol derivative prepared using 2-adamantane. Its NMR spectrum still retains the signals related to aromatic ring hydrogen, phenolic hydroxyl active hydrogen, benzylic CH and NH, but the signal in the adamantane skeleton region has changed to some extent compared with Preparation Example 1, indicating that the chemical environment of the cage-like skeleton has changed after the adamantane linkage site is changed.

[0064] Preparation Examples 4 and 5 are bisphenol derivatives prepared using 2,4'-dihydroxybenzophenone and 2,2'-dihydroxybenzophenone, respectively. In their 1H NMR spectra, the aromatic region no longer shows the typical two sets of symmetrical double peaks, but instead shows multiple sets of aromatic hydrogen signals, indicating that the introduction of the dihydroxybenzophenone isomer has changed the substitution mode of the aromatic ring. More aromatic carbon signals also appear in their 1C NMR spectra, further proving the formation of the target isomer structure.

[0065] Example 6 prepared an N-adamantane methyl-substituted tertiary amine bisphenol derivative. In its 1H NMR spectrum, the broad NH peak disappeared, indicating that the secondary amine structure had further transformed into a tertiary amine structure. An N-CH2-Ad related signal appeared at 2.75-3.10 ppm, an Ar2CH-N benzylic CH signal appeared at 4.9-5.1 ppm, and a significantly enhanced adamantane skeleton hydrogen signal appeared at 1.45-2.20 ppm. Since this product molecule contains two adamantane structural units, the peak intensity in the 1.45-2.20 ppm region of the spectrum is significantly higher than the aromatic region signal, consistent with the target structural characteristics. In its 1C NMR spectrum, an N-CH2-Ad related carbon signal appeared near 57 ppm, an Ar2CH-N carbon signal appeared near 69 ppm, and newly added or enhanced adamantane skeleton carbon signals appeared in the ranges of 42-56 ppm and 29-49 ppm, indicating that the secondary amine structure had undergone a reductive amination reaction with 1-adamantaneformaldehyde to form an N-adamantane methyl-substituted structure.

[0066] In summary, the 1H NMR and 1C NMR spectra of the products obtained in the aforementioned preparation examples 1-6 are consistent with the target structures, indicating that the secondary amine type, tertiary amine type, and adamantane amine-containing bisphenol derivatives with different isomer substitutions and different N-substituted groups described in this invention have been successfully prepared.

[0067] Experimental Example 2 This experimental example performs basic performance tests on the bisphenol monomers containing adamantane amino groups obtained in the aforementioned preparation examples 1-2.

[0068] In this experimental example, high-performance liquid chromatography (HPLC), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) were used to test the basic properties of the obtained monomers. HPLC was used to confirm monomer purity; DSC was used to determine the melting point; and TGA was used to evaluate the thermal stability of the monomers. The test data are shown in Table 1 below.

[0069] Table 1. Structure and basic properties of bisphenol monomers containing adamantaneamine group.

[0070] As shown in Table 1, the bisphenol monomers containing adamantaneamine groups prepared by this invention can be obtained in high yields via a low-cost raw material route, and the products exhibit high purity and good thermal stability. Specifically, the secondary amine monomer retains the NH structure, which is more conducive to improving the metal-metal interfacial bonding force and the epoxy ring-opening reactivity; the tertiary amine monomer does not contain NH bonds, making it more suitable for polycondensation systems such as polyesters, polyethers, and polyetherketones where reduced active hydrogen side reactions and hygroscopic risks are required. These results demonstrate that this invention can obtain both secondary and tertiary amine bisphenol monomers containing adamantaneamine groups via the same low-cost raw material route, exhibiting strong structural designability and application scalability.

[0071] Example 1 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a semi-crystalline polyaryletherketone copolymer containing 3 mol% adamantane-amine bisphenol monomer. Here, 3 mol% refers to the proportion of adamantane-amine bisphenol monomer in the total bisphenol monomer, i.e., adding 3 mol% adamantane-amine bisphenol monomer and 97 mol% hydroquinone to form the required bisphenol monomer for the reaction. The interpretation of proportions in the following embodiments is the same.

[0072] To a 250 mL four-necked flask equipped with a mechanical stirrer, nitrogen delivery tube, thermometer, and water separator, add 10.680 g (0.097 mol) of hydroquinone, 1.091 g (0.003 mol) of the monomer obtained in Preparation Example 2, 21.820 g (0.100 mol) of 4,4'-difluorobenzophenone, 15.203 g (0.110 mol) of anhydrous potassium carbonate, and 120.0 g of diphenyl sulfone.

[0073] Stirring was started and nitrogen was purged for 30 minutes. Then, under nitrogen protection, the temperature was raised to 160°C and held for 1 hour to allow hydroquinone monomer, adamantane aminodiphenol monomer and potassium carbonate to form salts and remove moisture from the reaction system by evaporation. Then, the temperature was raised to 220°C for prepolymerization reaction for 1 hour. The temperature was then raised to 280°C for polycondensation reaction for 2 hours. Finally, the temperature was raised to 300°C for high-temperature polycondensation for 1 hour.

[0074] After the reaction was completed, the mixture was cooled to room temperature under nitrogen protection. The resulting solid material was pulverized to a particle size of less than 3 mm and then subjected to ethanol reflux extraction, hot deionized water washing, dilute hydrochloric acid aqueous solution washing, and deionized water washing in sequence to remove small organic molecules such as diphenyl sulfone and oligomers, as well as inorganic salts such as carbonates and fluorides. The solid was then dried in a vacuum oven at 120 °C for 12 h to obtain a polyaryletherketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 3 mol%, denoted as PAEK-NCAd-3.

[0075] Example 2 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a semi-crystalline polyarylether ketone copolymer containing 5 mol% adamantane amino bisphenol.

[0076] This embodiment refers to the preparation method described in Example 1, except that the amount of hydroquinone used is 10.460 g (0.095 mol), and the amount of monomer obtained in Preparation Example 2 is 1.818 g (i.e., 0.005 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyarylether ketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 5 mol% is obtained, denoted as PAEK-NCAd-5.

[0077] Example 3 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a semi-crystalline polyarylether ketone copolymer containing 10 mol% adamantane aminodiphenol.

[0078] This embodiment refers to the preparation method described in Example 1, except that the amount of hydroquinone used is 9.910 g (0.090 mol), and the amount of monomer obtained in Preparation Example 2 is 3.635 g (i.e., 0.010 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyarylether ketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 10 mol% is obtained, denoted as PAEK-NCAd-10.

[0079] Example 4 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a semi-crystalline polyarylether ketone copolymer containing 15 mol% adamantane aminodiphenol.

[0080] This embodiment refers to the preparation method described in Example 1, except that the amount of hydroquinone used is 9.359 g (i.e., 0.085 mol), and the amount of monomer obtained in Preparation Example 2 is 5.453 g (i.e., 0.015 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyarylether ketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 15 mol% is obtained, denoted as PAEK-NCAd-15.

[0081] Example 5 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a semi-crystalline polyarylether ketone copolymer containing 20 mol% adamantane aminodiphenol.

[0082] This embodiment refers to the preparation method described in Example 1, except that the amount of hydroquinone used is 8.809 g (i.e., 0.080 mol), and the amount of monomer obtained in Preparation Example 2 is 7.270 g (i.e., 0.020 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyarylether ketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 20 mol% is obtained, denoted as PAEK-NCAd-20.

[0083] Example 6 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a polyarylether ketone copolymer containing 50 mol% adamantane aminodiphenol.

[0084] This embodiment refers to the preparation method described in Example 1, except that the amount of hydroquinone used is 5.506 g (i.e., 0.050 mol), and the amount of monomer obtained in Preparation Example 2 is 18.175 g (i.e., 0.050 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyarylether ketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 50 mol% is obtained, denoted as PAEK-NCAd-50.

[0085] Example 7 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a polyarylether ketone copolymer containing 75 mol% adamantane aminodiphenol.

[0086] This embodiment refers to the preparation method described in Example 1, except that the amount of hydroquinone used is 2.753 g (i.e., 0.025 mol), and the amount of monomer obtained in Preparation Example 2 is 27.263 g (i.e., 0.075 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyarylether ketone copolymer with an Ad-N(CH3)-CH(PhOH)2 content of 75 mol% is obtained, denoted as PAEK-NCAd-75.

[0087] Example 8 This embodiment is based on the bisphenol monomer Ad-N(CH3)-CH(PhOH)2 obtained in Preparation Example 2 above, to prepare a polyarylether ketone polymer containing 100 mol% adamantane aminodiphenol, i.e., without adding hydroquinone.

[0088] This embodiment refers to the preparation method described in Example 1, except that hydroquinone is not used, and the amount of monomer obtained in Preparation Example 2 is 36.350 g (i.e., 0.100 mol). The remaining raw materials and operating steps are the same as in Example 1. Finally, a polyaryletherketone polymer with an Ad-N(CH3)-CH(PhOH)2 content of 100 mol% is obtained, denoted as PAEK-NCAd-100.

[0089] Example 9 This embodiment is based on the bisphenol monomer Ad-NH-CH(PhOH)2 obtained in Preparation Example 1 above, to prepare a semi-crystalline polyarylether ketone copolymer containing 15 mol% adamantane aminodiphenol.

[0090] This embodiment refers to the preparation method described in Example 4, except that the adamantane-amine bisphenol monomer Ad-N(CH3)-CH(PhOH)2 in the polymerization raw materials is replaced with Ad-NH-CH(PhOH)2, and the amount added is 5.242 g (i.e., 0.015 mol). The remaining raw materials and operating steps are the same as in Example 4. Finally, a polyaryletherketone copolymer with an Ad-NH-CH(PhOH)2 content of 15 mol% is obtained, denoted as PAEK-NHAd-15.

[0091] Example 10 This embodiment is based on the bisphenol monomer Ad-NH-CH-2,4'-(PhOH)2 obtained in Preparation Example 4 above, to prepare a semi-crystalline polyarylether ketone copolymer containing 15 mol% adamantane aminodiphenol.

[0092] This embodiment refers to the preparation method described in Example 4, except that the adamantane-amine bisphenol monomer Ad-N(CH3)-CH(PhOH)2 in the polymerization raw materials is replaced with Ad-NH-CH-2,4'-(PhOH)2, and the amount added is 5.242 g (i.e., 0.015 mol). The remaining raw materials and operating steps are the same as in Example 4. Finally, a polyarylether ketone copolymer with an Ad-NH-CH-2,4'-(PhOH)2 content of 15 mol% is obtained, denoted as PAEK-NHAd-2,4'-15.

[0093] Comparative Example 1 This comparative example prepared a conventional PEEK resin without the introduction of bisphenol monomers containing adamantaneamine groups, which served as a reference sample.

[0094] To a 250 mL four-necked flask equipped with a mechanical stirrer, nitrogen delivery tube, thermometer, and water separator, add 11.011 g of hydroquinone (0.100 mol), 21.820 g of 4,4'-difluorobenzophenone (0.100 mol), 15.203 g of anhydrous potassium carbonate (0.110 mol), and 120.0 g of diphenyl sulfone. Prepare an unmodified PEEK resin, denoted as PAEK-0, using the nucleophilic substitution polycondensation and post-treatment method described in Example 1.

[0095] This sample is used to illustrate that although conventional PEEK has high heat resistance and mechanical strength, it has a high melting point and high melt processing temperature, and does not contain adamantane cage structure and amino interfacial interaction sites. Therefore, it is inferior to the polymer obtained in the examples in terms of low melting point processability, low dielectric properties, wear resistance and copper adhesion.

[0096] Comparative Example 2 This comparative example prepared polyarylether ketones modified by copolymerization of 1,3-bis(4-hydroxyphenyl)adamantane at 15 mol%.

[0097] This comparative example follows the preparation method of Example 4, except that: Ad-NH-CH(PhOH)2 is replaced with 1,3-bis(4-hydroxyphenyl)adamantane, with an addition amount of 0.015 mol, corresponding to a mass of 4.806 g; the amount of hydroquinone used is 9.359 g, or 0.085 mol; and the 4,4'-difluorobenzophenone, anhydrous potassium carbonate, diphenyl sulfone, and operating steps are consistent with Example 4. The final product is a 15 mol% copolymerized modified polyarylether ketone of 1,3-bis(4-hydroxyphenyl)adamantane, denoted as PAEK-13DHAd-15.

[0098] Comparative Example 3 This comparative example prepared polyarylether ketones modified by 15 mol% copolymerization of 2,2-bis(4-hydroxyphenyl)adamantane.

[0099] This comparative example follows the preparation method of Example 4, except that: Ad-NH-CH(PhOH)2 is replaced with 2,2-bis(4-hydroxyphenyl)adamantane, with an addition amount of 0.015 mol, corresponding to a mass of 4.806 g; the amount of hydroquinone used is 9.359 g, or 0.085 mol; and the 4,4'-difluorobenzophenone, anhydrous potassium carbonate, diphenyl sulfone, and operating steps are consistent with Example 4. The final product is a 15 mol% copolymerized modified polyarylether ketone of 2,2-bis(4-hydroxyphenyl)adamantane, denoted as PAEK-22DHAd-15.

[0100] Experimental Example 3 In this experimental example, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was used to characterize the structures of PAEK-NCAd-15 obtained in Example 4, PAEK-NCAd-100 obtained in Example 8, PAEK-NHAd-15 obtained in Example 9, PAEK-NHAd-2,4'-15 obtained in Example 10, PEEK obtained in Comparative Example 1, and PAEK-13DHAd-15 obtained in Comparative Example 2. The test range was 4000-650 cm⁻¹. -1 The attenuated total reflectance Fourier transform infrared spectrum of the polymer is attached. Figure 3 As shown.

[0101] As shown in the figure, the PEEK obtained in Comparative Example 1 is at 1652 cm. -1 An absorption peak for the C=O stretching vibration of aromatic ketone groups appears nearby, at 1595 cm⁻¹. -1 An absorption peak for the C=C skeletal vibration of aromatic rings appears nearby, and it is located at 1218 cm⁻¹. -1 The presence of COC-related absorption peaks in the vicinity indicates that the sample retains the typical polyarylether ketone backbone structure. The polyarylether ketone samples obtained in Examples 4, 8, 9, 10, and Comparative Example 2 all retained the aforementioned characteristic peaks of aromatic ketone groups, aromatic ring skeletons, and aromatic ether structures, indicating that the introduction of adamantane bisphenol monomers or adamantane diphenol monomers did not disrupt the basic chemical structure of the polyarylether ketone backbone.

[0102] Compared with the PEEK obtained in Comparative Example 1, the polymers obtained in Examples 4, 8, 9, 10, and Comparative Example 2 all showed a growth rate of 2910 cm⁻¹. -1 The presence of an aliphatic CH stretching vibration absorption peak associated with the adamantane structure indicates that the adamantane structure has indeed been introduced into the polyaryletherketone. The proportions of adamantane-amine-containing bisphenol monomers in PAEK-NCAd-15 obtained in Example 4, PAEK-NHAd-15 obtained in Example 9, and PAEK-NHAd-2,4'-15 obtained in Example 10 are similar to the proportion of adamantane-bisphenol monomers in the polymer obtained in Comparative Example 2; therefore, their 2910 cm⁻¹ peaks are similar. -1 The CH-related absorption intensity of the nearby adamantane is at a similar level to that of PAEK-13DHAd-15.

[0103] In the PAEK-NCAd-100 obtained in Example 8, the proportion of N-methylated tertiary amine adamantane bisphenol monomer in the bisphenol component is higher, therefore its 2910 cm⁻¹ is higher. -1The CH-related absorption intensity of adamantane was significantly stronger than that of Examples 4, 9, 10, and Comparative Example 2. Meanwhile, the peak shape of PAEK-NCAd-100 in the fingerprint region changed somewhat in the lower proportion of copolymerized samples, indicating that the high content and large volume of adamantane amino structural units affected the regularity of the polyaryletherketone chain segments and the local vibrational environment.

[0104] From the perspective of nitrogen-containing structural characteristics, both PAEK-NHAd-15 obtained in Example 9 and PAEK-NHAd-2,4'-15 obtained in Example 10 have a nitrogen content of 3315 cm⁻¹. -1 A broad peak related to the NH stretching vibration was observed nearby, while no obvious NH characteristic absorption was observed in PAEK-NCAd-15 obtained in Example 4, PAEK-NCAd-100 obtained in Example 8, PEEK obtained in Comparative Example 1, and PAEK-13DHAd-15 obtained in Comparative Example 2. This result is consistent with the actual monomer structure involved in the polymerization reaction. Furthermore, this demonstrates that the secondary and tertiary amine types of adamantaneamine bisphenol structures can be distinguished by infrared spectroscopy.

[0105] Furthermore, the polymers obtained in Examples 4, 8, 9, and 10 were subjected to a temperature of 1258 cm⁻¹. -1 Absorption peaks related to CN stretching vibrations were observed at all locations, while this feature was not obvious in PEEK obtained in Comparative Example 1 and PAEK-13DHAd-15 obtained in Comparative Example 2. These results indicate that, compared to unmodified PEEK and conventional adamantanediol-modified PAEK, the adamantaneamine bisphenol monomer-modified polyaryletherketone obtained in this invention does indeed introduce nitrogen-containing structural units.

[0106] Comparing PAEK-NHAd-15 obtained in Example 9 and PAEK-NHAd-2,4'-15 obtained in Example 10, it can be seen that both possess basic characteristic peaks such as NH, adamantane CH, aromatic ketone C=O, aromatic ring C=C, CN, and aromatic ether CO. However, since Example 10 uses adamantane bisphenol monomer derived from 2,4'-dihydroxybenzophenone, its aromatic ring substitution mode differs from that of Example 9. Therefore, the peaks at 1500-1450 cm⁻¹ are different. -1 1300-1150cm -1 and 900-700cm -1 Within the isofinite region, certain peak shapes and relative intensity differences were observed. This difference indicates that changes in the polymerization site affect the local environment of aromatic ring skeletal vibrations and CH vibrations in the polyaryletherketone chain.

[0107] In summary, monomers with different adamantane structures have been introduced into the polymers, and different proportions, structures, and linkage methods of the monomers all have discernible effects on the infrared spectra of the polymers.

[0108] Experiment Example 4 This experiment tested the thermal, dielectric, and mechanical properties of the polyaryletherketone polymers prepared in Examples 1-10 and Comparative Examples 1-3.

[0109] The resin materials obtained in Examples 1-10 and Comparative Examples 1-3 were vacuum dried at 150°C for 6 hours. Sheets with a thickness of 0.40 mm were hot-pressed using a flat vulcanizing machine for dielectric property testing, and sheets with a thickness of 1.0 mm were prepared for mechanical property and copper peel testing. The hot-pressed sheets were annealed at 200°C for 2 hours and then naturally cooled to room temperature.

[0110] Melting point and glass transition temperature were determined using differential scanning calorimetry (DSC). The tests were conducted under a nitrogen atmosphere at a heating rate of 10 °C / min. The sample was first heated from room temperature to 380 °C, held for 3 min to eliminate thermal history, then cooled to 50 °C, and then subjected to a second heating test at 10 °C / min. The glass transition temperature Tg from the second heating curve was recorded. g and melting peak temperature T m As a test result, samples that do not show a clear melting endothermic peak are recorded as "no clear melting peak".

[0111] Thermal stability was tested using thermogravimetric analysis (TGA). The test was conducted under a nitrogen atmosphere with a heating rate of 10 °C / min, and the temperature range was from room temperature to 800 °C. The temperature at which the sample mass loss reached 5% was recorded as the 5% thermogravimetric temperature T. d (5%). The higher the 5% thermogravimetric temperature, the better the thermal stability of the material.

[0112] Crystallinity was determined using a combination of differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The presence of obvious melting peaks was observed in the DSC, while the XRD scan range was 5°–40° at a scan rate of 2° / min. Based on the presence and intensity changes of characteristic crystallization diffraction peaks of PEEK-type polyaryletherketones, the samples were categorized as high, medium, low, or none.

[0113] Dielectric properties were measured using an impedance analyzer or dielectric spectrometer. Before testing, the dielectric test sheet samples were vacuum dried at 120-150℃ for 4-6 hours, then cooled to room temperature in a desiccator and tested as soon as possible to obtain the dielectric properties of the material in its dry state. The test frequency was 1MHz, the test temperature was 25℃, and the sample thickness was 0.40mm. At least three parallel samples were tested for each group, and the average value was recorded. The dielectric constant Dk and dielectric loss Df were recorded.

[0114] Mechanical properties were tested using a universal testing machine. The hot-pressed sheet was cut into standard dumbbell or strip-shaped specimens. Tensile testing was conducted at a speed of 5 mm / min, and tensile strength and elongation at break were recorded. At least five parallel samples were tested for each group, and the average value was taken. Tensile strength was used to evaluate the material's load-bearing capacity, and elongation at break was used to evaluate the material's deformation capacity and toughness during tensile testing.

[0115] The specific test data is shown in Table 2 below.

[0116] Table 2 Thermal, dielectric and mechanical properties of polyaryletherketone copolymers

[0117] Table 2 shows that conventional PEEK has a high melting point, high thermal stability, and good mechanical properties, but its dielectric constant and dielectric loss are relatively high, and its high melting point is not conducive to reducing the melt processing temperature. With the proportion of the N-methylated tertiary amine adamantaneamine bisphenol monomer Ad-N(CH3)-CH(PhOH)2 increased from 3 mol% to 20 mol%, the TL of the obtained PAEK-NCAd series copolymers... g Gradually increase, T m The gradual decrease indicates that the introduction of adamantane cage structure and tertiary amine nitrogen-containing structural units increases the local rigidity of the chain segment, while weakening the crystallization stacking ability of PEEK-type regular chain segments.

[0118] At low to medium introduction ratios, the PAEK-NCAd series retains a certain degree of semi-crystalline properties, with PAEK-NCAd-15 exhibiting the best overall balance. Compared to unmodified PEEK, PAEK-NCAd-15 has a higher Tg. m The temperature decreased from 343℃ to 306℃, Dk decreased from 3.22 to 2.83, and Df decreased from 0.0048 to 0.0031, indicating that the appropriate introduction of N-methylated adamantaneamine bisphenol structure is beneficial to reducing the melt processing temperature and dielectric polarization response of polyaryletherketone. Meanwhile, PAEK-NCAd-15 still maintains a tensile strength of 84 MPa and an elongation at break of 12%, demonstrating a good overall balance between low dielectric properties, melt processability, and mechanical properties.

[0119] When the proportion of Ad-N(CH3)-CH(PhOH)2 introduced was further increased to over 50 mol%, the regularity of the polymer chain segments decreased significantly, and the samples no longer exhibited obvious melting peaks, indicating that they gradually transformed from a semi-crystalline structure to a low-crystallinity or amorphous structure. Although the high-proportion samples PAEK-NCAd-50, PAEK-NCAd-75, and PAEK-NCAd-100 had higher T... gWhile exhibiting better solution processing potential, the tensile strength and elongation at break decrease due to the significant weakening of the ordered PEEK segments, while dielectric loss increases. Therefore, high-content adamantaneamine bisphenol monomers are more suitable for solution processing or coating film systems, rather than as a preferred overall composition for melt-processed structural components.

[0120] The PAEK-NHAd-15 obtained in Example 9 was a 15 mol% secondary amine type adamantaneamine bisphenol monomer-modified PAEK. Compared with PAEK-NCAd-15, PAEK-NHAd-15 has a higher Tg... d (5%) is relatively low, but T g and T m However, the values ​​are slightly higher, mainly because the secondary amine structure retains the NH bond, which can form hydrogen bonds with groups such as carbonyl or hydroxyl groups, increasing the interaction between molecular chains. Furthermore, the NH bond exhibits stronger hygroscopic and polarizing effects, therefore, the Dk and Df values ​​of PAEK-NHAd-15 are higher than those of PAEK-NCAd-15. Therefore, for applications with higher dielectric requirements, N-methylated adamantane bisphenol monomers are preferred; for applications with higher interfacial strength requirements, secondary amine adamantane bisphenol monomers containing NH bonds are preferred.

[0121] The polymer obtained in Example 10 was PAEK modified with 15 mol% of 2,4'-isomerized secondary amine adamantaneamine bisphenol monomer. Compared with PAEK-NCAd-15, PAEK-NHAd-2,4'-15 had a higher Tg. g Increase, T m However, it has decreased. This is because hydrogen bonding interactions exist within the polymer, restricting the relative movement of the molecular chains, T g The T value increases; however, the 2,4'-substitution structure further reduces segment symmetry and regularity, thus decreasing the polymer's crystallinity. m The decrease in Dk and Df values ​​provides a feasible basis for controlling melt behavior and solubility. Furthermore, the Dk and Df values ​​of PAEK-NHAd-2,4'-15 are also higher than those of PAEK-NHAd-15. These results indicate that adamantaneamine bisphenol monomers prepared from dihydroxybenzophenone with different substitution sites can be used for the preparation of PAEK, and the crystallinity, melt behavior, and dielectric properties of the polymer can be controlled by the substitution position.

[0122] The PAEK-13DHAd-15 and PAEK-22DHAd-15 polymers obtained in Comparative Examples 2 and 3 used conventionally available 1,3-bis(4-hydroxyphenyl)adamantane and 2,2-bis(4-hydroxyphenyl)adamantane as comonomers, respectively. The Dk and Df values ​​of the polymer PAEK-NCAd-15 obtained in Example 4 are close to those of the polymers obtained in Comparative Examples 2 and 3. This indicates that although conventional adamantine-diphenol-modified polyaryletherketones have a slight advantage in reducing dielectric polarization, their molecules do not contain amino interfacial interaction sites. Therefore, the advantage of PAEK-NCAd-15 and PAEK-NHAd-15 of this invention lies not in the absolute lowest single dielectric property, but in the comprehensive balance between low melting point processing, low dielectric properties, thermal stability, mechanical properties, and nitrogen-containing interfacial interaction capabilities.

[0123] Experimental Example 5 This experiment tested the abrasion resistance, copper bonding strength, and processing suitability of the PAEK polymers prepared in Examples 1-10 and Comparative Examples 1-3.

[0124] Before testing, each resin sample was vacuum dried at 150℃ for 6 hours to remove adsorbed moisture. For melt-processable samples, test sheets were prepared by hot pressing using a flat vulcanizing machine. The hot pressing temperature was adjusted appropriately according to the melting point of the material, usually 30-50℃ above the melting point. For polyaryletherketone samples with high Ad-N(CH3)-CH(PhOH)2 content but no obvious melting peak but solution processability, sheet or coating samples were prepared by casting an N-methylpyrrolidone solution followed by heat treatment. Before testing, the samples were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours.

[0125] Wear resistance was evaluated using the Taber abrasion method. Resin was prepared into circular samples with a diameter of 100 mm and a thickness of 1.0 mm. CS-10 grinding wheels were used, with a load of 500 g on each wheel, a rotation speed of 60 r / min, and 1000 abrasion cycles. The sample mass was weighed before and after the test, and the wear mass Δm was calculated in mg. At least three parallel samples were tested for each group, and the average value was taken. Lower wear mass indicates better wear resistance.

[0126] Copper adhesion was evaluated using a 180° peel test. A clean copper foil with a thickness of 35 μm was selected as the substrate, and sequentially cleaned with acetone, ethanol, and deionized water, then dried. For melt-processable samples, dried resin powder or a pre-made film was placed on the copper foil surface and hot-pressed at a suitable temperature for 5 MPa for 5 min, controlling the polyaryletherketone layer thickness to be 100 ± 10 μm. For samples with high adamantane content and primarily solution-processed, a 10-15% (w / w) resin solution was coated onto the copper foil surface, followed by pre-drying at 80°C, drying at 150°C, and heat treatment at 220-230°C to obtain a coating thickness of 100 ± 10 μm. The composite sample was cut into 10 mm wide test strips and subjected to a 180° peel test at 50 mm / min on a universal testing machine. The average peel force during the stable peeling phase was recorded, and the copper peel strength was calculated as peel force / sample width, in N·mm. -1 Each sample group should be tested with no fewer than 5 parallel samples, and the average value should be taken.

[0127] Processing suitability was evaluated using both melt processing and solution processing methods. Melt processing involves hot pressing dried resin at a suitable material temperature or processing it using a single-screw extruder; solution processing involves casting an N-methylpyrrolidone solution followed by heat treatment to obtain the corresponding film or sheet. The surface defects such as gelation, bubbles, cracks, voids, and warping were compared between the two methods. The preparation method with superior properties was selected as the preferred preparation method for the corresponding polyaryletherketone polymer.

[0128] The specific test results are shown in Table 3 below.

[0129] Table 3. Abrasion resistance, copper bonding strength, solubility, and recommended processing methods of polyaryletherketone copolymers.

[0130] As shown in Table 3, the unmodified PEEK obtained in Comparative Example 1 has good basic mechanical and heat resistance properties, but its wear mass is 12.1 mg and its copper peel strength is only 1.1 N·mm. -1 Furthermore, it is insoluble in NMP, indicating that although conventional PEEK is suitable for high-temperature melt processing, its molecular structure does not contain adamantane cage structure and nitrogen-containing interfacial interaction sites. Therefore, there is still room for improvement in terms of wear resistance, copper conductor bonding strength, and solution processing applicability.

[0131] As the proportion of the N-methylated tertiary amine adamantaneamine bisphenol monomer Ad-N(CH3)-CH(PhOH)2 introduced increased from 3 mol% to 15 mol%, the wear mass of the PAEK-NCAd series gradually decreased from 10.8 mg to 6.3 mg, and the copper peel strength increased from 1.2 N·mm. -1 Increased to 2.2 N·mm-1 The results indicate that the introduction of an appropriate amount of adamantane cage structure is beneficial to improving the local rigidity and surface wear resistance of the polyaryletherketone chain segments, while the tertiary amine-type nitrogen-containing structural units can act as hydrogen bond acceptors or Lewis acid-base interaction sites, enhancing the interaction between the polymer and the copper surface oxide layer or polar interface. Combined with the thermal and dielectric property results in Experiment 4, it can be seen that PAEK-NCAd-15 exhibits a good overall balance between low dielectric properties, melt processability, wear resistance, and copper adhesion.

[0132] When the proportion of Ad-N(CH3)-CH(PhOH)2 introduced was increased to 20 mol%, the copper peel strength of PAEK-NCAd-20 continued to increase to 2.4 N·mm. -1 However, the wear quality is slightly higher than that of PAEK-NCAd-15. This indicates that the increase of tertiary amine adamantane amino group structural units is beneficial to enhancing the copper interface effect, but excessive introduction will further weaken the crystalline stacking and semi-crystalline structure contribution of PEEK-type regular segments, thus causing the wear resistance to begin to decline.

[0133] When the proportion of Ad-N(CH3)-CH(PhOH)2 reaches 50 mol% or higher, PAEK-NCAd-50, PAEK-NCAd-75, and PAEK-NCAd-100 are soluble or readily soluble in NMP, indicating that a high proportion of large-volume adamantaneamine structural units significantly reduces the regularity and crystallinity of polyaryletherketone (PAEK) chains, making them more suitable for solution coating and casting. Simultaneously, the wear mass of the high-proportion samples further increased from 12.2 mg to 19.8 mg, indicating that the wear resistance of the material decreases after the regularized segments of semi-crystalline PEEK are significantly weakened. Therefore, the high-content PAEK-NCAd series is more suitable for solution-processed insulating coatings, metal surface coatings, or thin film materials, and not as a preferred composition for melt-processed structural components requiring high wear resistance.

[0134] The PAEK-NHAd-15 obtained in Example 9 is PAEK modified with 15 mol% secondary amine-type adamantaneamine bisphenol monomer. Compared with PAEK-NCAd-15, the wear mass of PAEK-NHAd-15 was further reduced from 6.3 mg to 5.9 mg, and the copper peel strength was reduced from 2.2 N·mm. -1 Increased to 2.9 N·mm -1This result indicates that the secondary amine type Ad-NH-CH(PhOH)2 retains the NH structure, enabling it to form hydrogen bonds, dipoles, coordination groups, or Lewis acid-base interactions with the oxide layer, polar groups, or hydroxyl groups on the copper conductor surface. This enhances the interfacial adhesion between the polyaryletherketone (PAEK) coating and the copper conductor, as well as its own wear resistance. Combined with the results in Experiment 4 showing that PAEK-NHAd-15 has a higher dielectric constant and dielectric loss than PAEK-NCAd-15, it can be concluded that the secondary amine structure is more suitable for insulating coatings or metal interface reinforcement applications where higher adhesion to the copper conductor is required, while the tertiary amine structure is more suitable for applications with more stringent requirements for low dielectric constant and low moisture absorption.

[0135] The PAEK-NHAd-2,4'-15 obtained in Example 10 also contains 15 mol% of secondary amine-type adamantane bisphenol structural units, and its copper peel strength is 2.7 N·mm. -1 The wear quality of PAEK-NHAd-2,4'-15 was significantly higher than that of unmodified PEEK and traditional adamantine-modified samples, indicating that the secondary amine-type nitrogen-containing interfacial interaction sites can still effectively improve the copper interfacial bonding. However, due to the reduced monomer symmetry and polymer chain segment regularity caused by the 2,4'-isomer structure, PAEK-NHAd-2,4'-15 had a higher wear quality than PAEK-NHAd-15 and showed partial dissolution in NMP. This indicates that the isomerization structure is beneficial for improving chain segment irregularity and solution processing adaptability, but it will weaken the semi-crystalline structure and wear resistance of the material to some extent.

[0136] Comparative Examples 2 and 3 yielded PAEK-13DHAd-15 and PAEK-22DHAd-15, respectively, using conventional 1,3-bis(4-hydroxyphenyl)adamantane and 2,2-bis(4-hydroxyphenyl)adamantane as comonomers. Compared to unmodified PEEK, the wear mass decreased from 12.1 mg to 7.8 mg and 8.4 mg, respectively, indicating that the conventional adamantine-diphenol structure can also improve the wear resistance of the material through a rigid cage-like framework. However, the copper peel strength was only 1.3 N·mm. -1 and 1.2 N·mm -1 The value was significantly lower than that of PAEK-NCAd-15, PAEK-NHAd-15, and PAEK-NHAd-2,4'-15. This result indicates that although the introduction of traditional adamantanediol is beneficial for reducing dielectric polarization and improving wear resistance, its molecular structure does not contain nitrogen-containing interfacial interaction sites such as tertiary or secondary amines, making it difficult to effectively improve the bonding force between polyaryletherketone and copper conductors.

[0137] In summary, Table 3 shows that the adamantane amine bisphenol monomer-modified polyaryletherketone of this invention can not only improve the wear resistance of the material through the adamantane cage structure, but also enhance the interaction between the polymer and copper conductors or polar interfaces through the amine structure. Among them, PAEK-NCAd-15 has a good overall balance between melt processability, low dielectric properties, wear resistance and copper adhesion; PAEK-NHAd-15 has higher copper adhesion and is suitable for scenarios with higher requirements for metal interface bonding; PAEK-NCAd-50, PAEK-NCAd-75 and PAEK-NCAd-100 are more suitable for solution coating and casting film applications.

[0138] Application Example 1 In this application example, PAEK-NCAd-15 prepared in Example 4 above is used for the processing of the insulating outer coating material of flat copper wire melt extrusion.

[0139] PAEK-NCAd-15 resin was dried in a vacuum oven at 150℃ for 6 hours to remove adsorbed water and residual volatiles. Flat copper wire with a width of 4.0 mm and a thickness of 1.5 mm was selected as the conductor. The flat copper wire was cleaned by wiping with acetone and ethanol sequentially, and then dried at 120℃ for 30 minutes. The dried PAEK-NCAd-15 resin was added to a single-screw cable coating extruder for continuous extrusion coating. The extruder temperatures were: Zone 1: 295℃, Zone 2: 315℃, Zone 3: 325℃, Die Head: 335℃, Die No.: 335℃, Screw Speed: 25 r / min, Coating Speed: 10 m / min. The melt was uniformly coated onto the surface of the flat copper wire through the extrusion die, and then air-cooled and sized to obtain a continuous flat copper wire insulation coating.

[0140] The obtained PAEK-NCAd-15 outer coating had an average thickness of 120±10μm, with a smooth and continuous surface, free from obvious gelation, cracks, bubbles, and pinholes. A 3kV spark test was performed on a 30m continuous wire sample, and no penetration pinholes were found. After heat treatment at 200℃ for 2 hours, the outer coating did not show cracking, blistering, or significant delamination. A 180° peel test was used to evaluate the adhesion between the outer coating and the copper conductor; the average peel strength during the stable peeling stage was 2.1 N·mm. -1 The dielectric constant and dielectric loss of the outer coating at 1 MHz were measured using a dielectric spectrometer, and were found to be 2.85 and 0.0031, respectively. The withstand voltage performance of the insulation layer was evaluated using power frequency or DC breakdown tests, with a breakdown strength of 185 kV / mm.

[0141] Application Example 2 This application example uses the PAEK-NCAd-15 material obtained in Example 4 above to process a hot-pressed low-dielectric insulating film.

[0142] PAEK-NCAd-15 resin was dried in a vacuum oven at 150℃ for 6 hours. An appropriate amount of the dried resin was weighed and placed between two layers of polyimide release film, then hot-pressed into a film using a flat vulcanizing machine. The hot-pressing temperature was 335℃. After preheating for 5 minutes, a pressure of 10 MPa was applied and held for 8 minutes. The film was then cooled to below 180℃ under pressure and removed. After edge trimming, the resulting film was annealed at 200℃ for 2 hours to reduce residual internal stress during the hot-pressing process.

[0143] The obtained PAEK-NCAd-15 film has a smooth surface, uniform thickness, and no obvious bubbles, cracks, pores, or particle defects. The film thickness can be controlled within the range of 40-250 μm; in this application example, the tested film thickness was 104 ± 6 μm. The dielectric constant and dielectric loss of the film at 1 MHz were measured using a dielectric spectrometer, and were 2.83 and 0.0032, respectively. The withstand voltage performance of the insulation layer was evaluated using a power frequency or DC breakdown test, with a breakdown strength of 205 kV / mm. The mechanical properties of the film were evaluated using a tensile test, with a tensile strength and elongation at break of 81 MPa and 8%, respectively.

[0144] Application Example 3 This application example uses PAEK-NCAd-50 prepared in Example 6 above for solution-coated insulating layer processing.

[0145] PAEK-NCAd-50 resin was dried in a vacuum oven at 120℃ for 6 hours. The dried PAEK-NCAd-50 resin was weighed and added to N-methylpyrrolidone, and stirred at 80℃ for 6 hours to prepare a 15% (w / w) polymer solution. The resulting solution was filtered through a 0.45 μm filter membrane and then degassed under vacuum to obtain a uniform coating solution. The copper foil surface was sequentially cleaned with acetone, ethanol, and deionized water, and then dried at 120℃ for 30 minutes before use.

[0146] PAEK-NCAd-50 solution was applied to the copper foil surface using a dip-coating method. After coating, the sample was pre-dried at 80-100°C for 30 minutes to remove some of the solvent; subsequently, it was dried at 150°C for 30 minutes, then at 180°C for 1 hour, and finally heat-treated at 230°C for 30 minutes to further densify the coating. The coating and drying steps can be repeated as needed to obtain the desired insulating coating thickness. In this application example, the coating thickness obtained was 32 ± 5 μm.

[0147] The obtained PAEK-NCAd-50 coating is continuous and uniform, with no obvious pinholes, cracks, shrinkage cavities, or particle defects on the surface. Optical microscopy was used to observe the surface and cross-sectional morphology of the coating, revealing a continuous interface between the coating and the copper substrate without significant voids. Dielectric constant and dielectric loss of the outer layer at 1 MHz were measured using dielectric spectroscopy, yielding values ​​of 2.95 and 0.0068, respectively. The withstand voltage performance of the insulation layer was evaluated using power frequency or DC breakdown tests, with a breakdown strength of 160 kV / mm. A 180° peel test was used to evaluate the interaction between the coating and the copper substrate, with a peel strength of 2.7 N·mm. -1 .

[0148] In summary, as can be seen from the above experimental and application examples, the present invention prepares a polyaryletherketone copolymer that combines low dielectric constant, high thermal stability, enhanced metal bonding, and adjustable processing method by copolymerizing a low-cost bisphenol monomer containing an adamantaneamine group with raw materials such as 4,4'-difluorobenzophenone.

[0149] Compared with conventional PEEK, the copolymer obtained by this invention can lower the melting point and processing temperature, and improve the processing windows for melt extrusion, injection molding and hot pressing; the adamantane cage structure is beneficial to reducing the dielectric constant and dielectric loss of the material, and improving wear resistance and scratch resistance; the amine structure can improve the glass transition temperature of the polymer and the bonding force with copper conductors through hydrogen bonding, dipole, coordination or Lewis acid-base interaction.

[0150] Compared to polyaryletherketones modified by copolymerization of 1,3-bis(4-hydroxyphenyl)adamantane and 2,2-bis(4-hydroxyphenyl)adamantane, the bisphenol monomer modification system containing adamantane amine structure of this invention not only introduces the low-polarity rigid structure of adamantane, but also further introduces nitrogen-containing interfacial interaction sites not found in traditional adamantane diphenols. The secondary amine structure is more conducive to improving copper bonding and dimensional stability; the tertiary amine structure is more conducive to reducing the risk of active hydrogen side reactions and improving dielectric loss and hygroscopic stability. Therefore, the advantage of the material of this invention lies not in the absolute lowest single dielectric index, but in the comprehensive balance between low dielectric, thermal stability, wear resistance, copper bonding, and processing performance.

[0151] In the modified polyaryletherketone polymer of this invention, when the Ad-N(CH3)-CH(PhOH)2 content is 10-20 mol%, especially around 15 mol%, the resulting polymer exhibits superior overall performance in terms of dielectric properties, thermal stability, dimensional stability, metal bonding strength, abrasion resistance, and melt processability. This makes it suitable for applications such as flat copper wire sheathing, electromagnetic wire insulation, injection-molded insulating structural parts, and hot-pressed insulating films. When the Ad-N(CH3)-CH(PhOH)2 content is above 50 mol%, the material's solubility is significantly improved, making it even more suitable for solution coating, casting, and thin-layer insulating coatings.

[0152] Therefore, this invention provides a low-cost adamantane-amine-based polyaryletherketone modification route with industrialization potential, which can be used in fields such as high-performance electrical insulation materials, low-dielectric materials, wear-resistant materials, metal surface coating materials, and high-performance engineering plastic materials.

[0153] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A polyarylether ketone modified with adamantane bisphenol monomer, characterized in that, The polymerization raw materials for the modified polyarylether ketone include bisphenol monomers, dihaloaromatic ketone monomers, and salt-forming agents. The bisphenol monomer includes adamantane bisphenol monomer having the structure shown in formulas (I)-(II): 、 (Ⅰ) (Ⅱ) in: R1, R2, R3, and R4 are independently H, -OH, or C1-C4 alkyl groups, and there is one and only one -OH group between R1 and R2, and one and only one -OH group between R3 and R4. R5 and R6 are independently H or C1-C4 alkyl groups; R7 is H or a C1-C4 alkyl or adamantane methyl group.

2. The polyarylether ketone modified with adamantane bisphenol monomer according to claim 1, characterized in that, The adamantane bisphenol monomer comprises one of the following structures: 、 、 、 、 、 。 3. The polyaryletherketone modified with adamantane bisphenol monomer according to claim 1 or 2, characterized in that, The diphenol monomer, based on its total molar amount, comprises: The adamantane bisphenol monomer is 3-100 mol%; Dihydroxy aromatic monomers 0-97 mol% The dihydroxy aromatic monomer includes at least one of hydroquinone, resorcinol, or biphenyl.

4. The polyaryletherketone modified with adamantane bisphenol monomer according to claim 1 or 2, characterized in that: The molar ratio of the dihaloaromatic ketone monomer to the diphenol monomer is 0.995-1.005:1; And / or, the molar ratio of the salt-forming agent to the diphenol monomer is 1.02-1.3:

1.

5. The polyarylether ketone modified with adamantane bisphenol monomer according to claim 1 or 2, characterized in that: The dihaloaromatic ketone monomers include at least one of 4,4'-difluorobenzophenone, 4,4'-dichlorobenzophenone, 2,4-difluorobenzophenone, 4-fluoro-4'-chlorobenzophenone, 2-fluoro-4-chlorobenzophenone, 2-chloro-4-fluorobenzophenone, 1,4-bis(4-fluorobenzoyl)benzene or 1,3-bis(4-fluorobenzoyl)benzene; And / or, the salt-forming agent includes at least one of alkali metal carbonates, alkali metal hydroxides, or alkali metal alkoxides.

6. A method for preparing adamantaneamine bisphenol monomer-modified polyarylether ketone according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Under a protective atmosphere, a selected amount of the diphenol monomer, the dihaloaromatic ketone monomer, the salt-forming agent and the reaction solvent are mixed to obtain a mixture; (2) The mixture is heated to the first reaction temperature, so that the diphenol monomer and the salt-forming agent undergo the first reaction to form phenol salt, and the water in the system is removed; (3) Continue heating to the second reaction temperature to allow the phenolate and dihaloaromatic ketone monomers to undergo a second reaction, thereby obtaining a prepolymer; (4) Continue heating to the third reaction temperature to allow the prepolymer to undergo the third reaction, thereby obtaining the condensate; (5) Continue heating to the fourth reaction temperature to allow the condensate to undergo the fourth reaction, thereby obtaining the desired modified polyarylether ketone.

7. The method for preparing adamantane bisphenol monomer-modified polyarylether ketone according to claim 6, characterized in that: The first reaction temperature is 140-180℃, and the first reaction time is 1-3 hours; And / or, the second reaction temperature is 200-240℃, and the second reaction time is 1-3h; And / or, the third reaction temperature is 260-290℃, and the third reaction time is 0.5-12h; And / or, the fourth reaction temperature is 290-320℃, and the fourth reaction time is 0.5-12h; And / or, the reaction solvent includes at least one of polar aprotic solvents.

8. The method for preparing adamantane bisphenol monomer-modified polyarylether ketone according to claim 6 or 7, characterized in that, The method further includes the step of preparing the adamantane bisphenol monomer, comprising the following steps: (a) Under a protective atmosphere, dihydroxybenzophenone, adamantane, a first solvent and an acidic catalyst are mixed and subjected to a condensation reaction under heating conditions to obtain an imine intermediate; (b) Under a protective atmosphere, the imine intermediate, the first reducing agent, and the second solvent are mixed and a first reduction reaction is carried out; Adamantane bisphenol monomer with R7 as shown in formula (I) or (II) was obtained; (c) Optionally, an aldehyde compound corresponding to the selected R7 structure and a second reducing agent are added, and a second reduction reaction is carried out to obtain an adamantane bisphenol derivative in which R7 is a C1-C4 alkyl or adamantane methyl group as shown in formula (I) or (II).

9. The method for preparing adamantane bisphenol monomer-modified polyarylether ketone according to claim 8, characterized in that: The dihydroxybenzophenone raw material includes substituted or unsubstituted 4,4'-dihydroxybenzophenone, 2,4'-dihydroxybenzophenone or 2,2'-dihydroxybenzophenone; And / or, the adamantaneamine raw material includes substituted or unsubstituted 1-adamantaneamine, 2-adamantaneamine or its salts; And / or, the molar ratio of the dihydroxybenzophenone raw material to the adamantane raw material is 1:1.0-1.2; And / or, the acidic catalyst is a Lewis acid catalyst, including at least one of p-toluenesulfonic acid, trifluoromethanesulfonic acid, trifluoroacetic acid, boron trifluoride, or aluminum trichloride; And / or, the amount of the acidic catalyst added accounts for 1-1.5 mol% of the molar amount of the dihydroxybenzophenone raw material. And / or, the temperature of the heating condensation reaction is 130-160℃, and the reaction time is 6-12h; And / or, the first solvent includes at least one of toluene, xylene, or chlorobenzene; And / or, the method further includes the steps of neutralizing, washing and / or drying the imine intermediate shown in formula (III) or (IV); And / or, the first reducing agent or the second reducing agent independently includes at least one of sodium borohydride, sodium cyanoborohydride, sodium triacetoxyborohydride, and reducing formate; And / or, the molar ratio of the first reducing agent to the imine intermediate is 1-2:1; And / or, the molar ratio of the second reducing agent to the adamantane bisphenol derivative is 1-2:1; And / or, the aldehyde compounds include at least one of formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, or 1-adamantaneformaldehyde; And / or, the temperature of the first reduction reaction is 25-50°C, and the reaction time is 4-8 hours; And / or, the temperature of the second reduction reaction is 10-30℃, and the reaction time is 2-12h; And / or, the second solvent includes at least one of an alcohol solvent or an ether solvent.

10. The application of the adamantane bisphenol monomer-modified polyarylether ketone according to any one of claims 1-5 in the preparation of electrical insulating materials, low dielectric materials, wear-resistant materials, metal surface coating materials or high-performance engineering plastic materials.